Effects of Addition Clove Oil to Extra virgin Olive Oil on Microbial Activity for Use as Transformer Oil - Wibowo, Kusnanto Mukti; Royan, Royan; Roamdhona, Gema; Irmawanto, Rudi (Journal of Sustainable Materials Processing and Management, 2021)
Transformer oil is a liquid insulating material that is used as insulator and as a coolant in transformers. In this study, the addition of clove oil to extra virgin olive oil were performed to determine its effect on antibacterial activity and its usefulness in its ability as a transformer oil. The breakdown voltage test on transformer oil is carried out using various oil temperatures (room temperature and 90oC) because the oil temperature inside the transformer when working/operating can be different, which can be caused by disturbances, excessive loading, and temperature conditions outside the transformer. In addition, the presence of contamination caused by chemical interactions with windings and other solid insulation is catalyzed by high operating temperatures. That causes a gradual change in the original chemical properties of the oil and microbial growth that over time makes it ineffective for use. The method used in this research is by mixing 10%, 20%, 30%, 40%, and 50% of clove oil with extra virgin olive oil to determine the change in breakdown voltage and microbial activity. The test results found that, the addition of clove oil has a vital role in inhibiting bacterial growth. The more clove oil added, the better its antimicrobial properties.